Tata Tertib Sekolah Berperan Sebagai Pengendali Perilaku Siswa di SD Inpres Raja Kecamatan Morotai Selatan Barat - Oktovina Mabuka (Jurnal Ilmiah Wahana Pendidikan, 2021)
The objectives to be achieved in this study were to determine 1) the role of school discipline as controlling student behavior in SD Inpres Raja, Morotai Selatan Barat Subdistrict, 2) the influence of school discipline on the behavior of students of SD Inpres Raja, Morotai Selatan Barat Subdistrict. This type of research used in this research is qualitative research. The results of this study are, SD Inpres Raja implements discipline by using a control system, in addition to making it easier for teachers, this discipline is also felt to be able to shape and change student behavior for the better. By giving penalties for violating the rules and giving rewards for those who do good according to what is stated in the code of conduct. With this discipline, students are more careful in taking action, students must be more able to choose what is good for them and what is not good for them. Because with this discipline, students feel that they are always being watched so they are careful